Cinnamate-zinc layered hydroxide nanocomposite attenuates inflammatory response in raw 264.7 macrophages stimulated by lipopolysaccharide - Adewoyin, Malik (2014)
Cinnamic acid (CA) is a phytochemical originally derived from Cinnamomum cassia, a plant with anti-inflammatory, antioxidant, antitumour and antiulcerogenic activity. The intercalation of CA with a nano carrier, zinc layered hydroxide (ZLH) produced cinnamate zinc layered hydroxide (ZCA), which has been previously characterized. The intercalation is expected to improve the solubility and cell specificity of CA. Also, the nano carrier will protect CA from degradation and sustain its release. Nevertheless, the aim of the research is to evaluate the efficacy CA-ZLH in an in vitro model using RAW 264.7 macrophage cell line.In this study, the anti-inflammatory activity of ZCA, CA and ZLH and their capacity to modulate the release of NO, PGE2, IL-6, TNF-α, IL-1β and IL-10 in lipopolysaccharide-induced RAW 264.7 cells were evaluated. Additionally, the expression of pro-inflammatory enzymes cyclooxygenase-2, iNOS and transcription factor NF-κB were examined. Cytotoxicity tests were conducted to determine the concentration of ZCA, CA and ZLH toxic to RAW 264.7 cells. This was followed by treatment of confluent RAW 264.7 with ZCA, CA and ZLH for one hour prior to stimulation of cells with lipopolysaccharide (LPS) for 24 hours to trigger an inflammatory response. Griess reagent was added to an equal volume of culture supernatant to determine the amount of NO produced in the treated and control groups of cells. ELISA was used to measure levels of cytokines (TNF-α, IL-6, IL-1β, Il-10) and PGE2produced by cells pretreated with ZCA, CA and ZLH, followed by activation with LPS for 30 minutes, 2 hours, 4 hours and 24 hours. Cell lysates from ZCA, CA and ZLH- treated cells were also used for Western blotting analysis to evaluate protein expression of COX-2, iNOS and NF-κB.The cytotoxicity test conducted showed that cells exposed to 2.5, 5 and 10 μg/ml each of ZCA, CA and ZLH displayed more than 90% cell viability. These three concentrations were selected for subsequent assays. NO produced in cells treated with ZCA and CA were significantly lower than samples treated with LPS alone. In the cytokine assay, ZCA and CA also displayed significant inhibitory effect after 24 hours after LPS stimulation against pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6 and another inflammatory marker PGE2. The only anti-inflammatory cytokine in the design, IL-10 was significantly upregulated by ZCA as well as CA. Western blot analysis showed samples treated with ZCA and CA significantly inhibited the protein expression of COX-2, iNOS and NF-κB. Even thoughZCA is composed of only40.4% of CA, it displayed higher anti-inflammatory activity than 100% CA. However, ZLH did not show any significant activity. The enhanced activity of ZCA may be associated with the intercalation which has reduced the compound to a nano size.